2013
DOI: 10.1371/journal.pone.0075220
|View full text |Cite
|
Sign up to set email alerts
|

An Association between Air Pollution and Daily Outpatient Visits for Respiratory Disease in a Heavy Industry Area

Abstract: In this work we used daily outpatient data from the Landseed Hospital in a heavily industrial area in northern Taiwan to study the associations between daily outpatient visits and air pollution in the context of a heavily polluted atmospheric environment in Chung-Li area during the period 2007–2011. We test the normality of each data set, control for the confounding factors, and calculate correlation coefficient between the outpatient visits and air pollution and meteorology, and use multiple linear regression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
61
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(67 citation statements)
references
References 39 publications
3
61
0
3
Order By: Relevance
“…Particulate matter particles cause respiratory morbidity and mortality by inducing oxidative stress and infl ammation that lead to pulmonary anatomic and physiologic remodeling 19 . Association with PM 10 has been reported for asthma [20][21][22][23][24][25] , URTI and pneumonia 22 , COPD exacerbations [24][25][26][27][28] , as well as for all respiratory visits 20,29,30 . In our study, the number of patients with respiratory diseases (except for asthma) correlated with higher PM 10 concentrations, confi rming its role as the most powerful air pollutant generated by burning of fossil fuels in vehicles and other causes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Particulate matter particles cause respiratory morbidity and mortality by inducing oxidative stress and infl ammation that lead to pulmonary anatomic and physiologic remodeling 19 . Association with PM 10 has been reported for asthma [20][21][22][23][24][25] , URTI and pneumonia 22 , COPD exacerbations [24][25][26][27][28] , as well as for all respiratory visits 20,29,30 . In our study, the number of patients with respiratory diseases (except for asthma) correlated with higher PM 10 concentrations, confi rming its role as the most powerful air pollutant generated by burning of fossil fuels in vehicles and other causes.…”
Section: Discussionmentioning
confidence: 99%
“…NO 2 is associated with asthma visits 21,[23][24][25]29,33 , COPD 22,33,34 , URTI 22 , pneumonia 29 , as well as all respiratory ED visits 35,36 . Samoli et al found signifi cant association of NO 2 with total, cardiovascular and respiratory mortality 31 .…”
Section: Discussionmentioning
confidence: 99%
“…Conclusions different from this paper are drawn. For instance, NO and NO 2 are two main air pollutants that are positively associated with respiratory diseases [17], as CO and NO 2 in Qatar [18], and benzene in Drammen, Norway [15]. However, the data of PM 2.5 , NO, CO, and benzene was not collected until 2015 in China.…”
Section: Discussionmentioning
confidence: 99%
“…Young patients (0-15 years of age) were the most affected by air pollution and meteorology factors, followed by elder patients (age ≥66 years), and aged 16-65. A closer look at gender differences revealed that women were more affected than men in the young age group and in the eldest group, but men were more sensitive between ages 16 and 65 groups [152][153][154][155]. Other studies have also reported both women and elderly people to be more susceptible to die from air pollution than other population groups [153,156,157].…”
Section: Outdoor Air Pollution and Lung Healthmentioning
confidence: 98%